Optimal sizing of modular air-cooled condensers for CSP plants - Poullikkas, Andreas (2013)
In this work, a parametric optimization analysis of various innovative modular air-cooled condenser systems is carried out in order to identify the optimum system configuration and size to be used as the cooling system in a 50M We parabolic trough concentrated solar power (CSP) plant. The optimization analysis is conducted individually on a total of 17 different configurations and on a total of 8 different condenser sizes for each configuration. The results identify the optimum air cooled condenser configuration and size that can achieve the minimum CSP plant electricity unit cost.